The probiotic potential of lactic acid bacteria (LAB) isolated from naniura (a traditional Batak food) - Mato Hang (Hasanuddin University Food Science and Technology Study Program, 2021)
Naniura is a traditional Batak food that is made without going through a heating process, but is made through a fermentation process using acid and salt. The use of acid and salt acts as a preservative because it can inhibit the growth of pathogenic microbes and spoilage microbes. In addition, naniura fermentation has the potential to be a growth medium for lactic acid bacteria, most of which strains can act as probiotics. However, the potential for probiotic naniura is still rarely studied and studied, so this review article is made to examine the potential for probiotic naniura and the health effects that can be obtained. The writing of this journal uses the literature study method, namely by collecting information from various scientific sources. Several studies have shown that naniura contains lactic acid bacteria that can act as broad-spectrum antimicrobials and can specifically inhibit the growth of Salmonella typhi, Bacillus cereus, Clostridium botulinum, E. coli and S. aureus. Consuming probiotic foods can have a positive effect on health, including improving the quality of the digestive tract, increasing the immune system in the body and degrading lactose so that it can be used for lactose intolerant sufferers.